Evaluation of CYP3A‐mediated drug–drug interactions with romidepsin in patients with advanced cancer. (29th July 2015) - Laille, Eric; Patel, Manish; Jones, Suzanne F.; Burris, Howard A.; Infante, Jeffrey; Lemech, Charlotte; Liu, Liangang; Arkenau, Hendrik‐Tobias
Abstract: Two multicenter, single‐arm, single‐infusion, open‐label studies were conducted to evaluate the effect of ketoconazole (a strong CYP3A inhibitor) or rifampin (a strong CYP3A inducer) daily for 5 days on the pharmacokinetics (PK) and safety of romidepsin (8 mg/m 2 intravenous 4‐hour infusion for the ketoconazole study or a 14 mg/m 2 intravenous 4‐hour infusion for the rifampin study) in patients with advanced cancer. Romidepsin coadministered with ketoconazole (400 mg) or rifampin (600 mg) was not bioequivalent to romidepsin alone. With ketoconazole, the mean romidepsin AUC and Cmax were increased by approximately 25% and 10%, respectively. With rifampin, the mean romidepsin AUC and Cmax were unexpectedly increased by approximately 80% and 60%, respectively; this is likely because of inhibition of active liver uptake. For both studies, romidepsin clearance and volume of distribution were decreased, terminal half‐life was comparable, and median Tmax was similar. Overall, the safety profile of romidepsin was not altered by coadministration with ketoconazole or rifampin, except that a higher incidence and greater severity of thrombocytopenia was observed when romidepsin was given with rifampin. The use of romidepsin with rifampin and strong CYP3A inducers should be avoided. Toxicity related to romidepsin exposure should be monitored when romidepsin is given with strong CYP3A inhibitors.